Potential roles of melatonin and chronotherapy among the new trends in hypertension treatment - Simko, Fedor; Pechanova, Olga (Journal of pineal research, 2009)
The number of well-controlled hypertensives is unacceptably low worldwide. Respecting the circadian variation of blood pressure, nontraditional antihypertensives, and treatment in early stages of hypertension are potential ways to improve hypertension therapy. First, prominent variations in circadian rhythm are characteristic for blood pressure. The revolutionary MAPEC (Ambulatory Blood Pressure Monitoring and Cardiovascular Events) study, in 3000 adult hypertensives investigates, whether chronotherapy influences the cardiovascular prognosis beyond blood pressure reduction per se. Second, melatonin, statins and aliskiren are hopeful drugs for hypertension treatment. Melatonin, through its scavenging and antioxidant effects, preservation of NO availability, sympatholytic effect or specific melatonin receptor activation exerts antihypertensive and anti-remodeling effects and may be useful especially in patients with nondipping nighttime blood pressure pattern or with nocturnal hypertension and in hypertensives with left ventricular hypertrophy (LVH). Owing to its multifunctional physiological actions, this indolamine may offer cardiovascular protection far beyond its hemodynamic benefit. Statins exert several pleiotropic effects through inhibition of small guanosine triphosphate-binding proteins such as Ras and Rho. Remarkably, statins reduce blood pressure in hypertensive patients and more importantly they attenuate LVH. Addition of statins should be considered for high-risk hypertensives, for hypertensives with LVH, and possibly for high-risk prehypertensive patients. The direct renin inhibitor, aliskiren, inhibits catalytic activity of renin molecules in circulation and in the kidney, thus lowering angiotensin II levels. Furthermore, aliskiren by modifying the prorenin conformation may prevent prorenin activation. At present, aliskiren should be considered in hypertensive patients not sufficiently controlled or intolerant to other inhibitors of renin-angiotensin system. Third, TROPHY (Trial of Preventing Hypertension) is the first pharmacological intervention for prehypertensive patients revealing that treatment with angiotensin II type 1 receptor blocker attenuates hypertension development and thus decreases the risk of cardiovascular events.
Keywords: hypertenze; Fumarates; Animals; statiny; antihypertenziva; Antihypertensive Agents; Humans; cirkadiánní rytmus; chronoterapie; melatonin; amidy; fumaráty; Amides; zvířata; Circadian Rhythm; Chronotherapy; Hypertension; Hydroxymethylglutaryl-CoA Reductase Inhibitors; lidé; Melatonin